Crystallization, morphology and self-assembly of double, triple and tetra crystalline block polymers. (April 2023) - Palacios, Jordana K.; Michell, Rose Mary; Müller, Alejandro J.
Abstract: This review compiles a comprehensive analysis of the crystallization behaviour and self-assembly of block copolymers with up to four potentially crystallizable phases. It covers the recent advances in block copolymer crystallization, focusing on several factors that affect the development of crystalline structures: melt strength, thermal transitions, cooling conditions, chemical nature, composition, and molecular architectures, such as linear, multiblocks, stars, and combs, as well as nanofillers and other additives. Block copolymers with different blocks can exhibit double, triple, and tetra crystalline structures. Following the crystallization behaviour of four different crystalline phases is very complex and relays on the interplay of the different blocks and the crystallization conditions. The self-assembly of four lamellar crystals is a unique structure with featured properties at the nanoscale. Depending on the segregation strength, the crystalline morphology can be either driven by phase separation resulting from polymer crystallization or set by a microdomain melt structure. Mixed lamellar arrangement in 3D spherulitic microscale structures or well-separated crystalline microdomains can be developed. The crystallization phenomena in block copolymers include enhanced nucleation, plasticizing and anti-plasticizing effects, fractionation, and soft and hard confinement. The crystallization kinetics is highly influenced by the chain dynamics of each block. Star block copolymers exhibit either enhanced or retarded crystallization rates depending on block position. Other external compounds, such as plasticizers and nanofillers, may enhance the crystallizability of block copolymers. Highlights: Review the recent advances in block copolymer crystallization with more than one crystallizable block. When multiple phases are prone to crystallize, the crystallization behavior becomes more intricate and complex. Melt strength, thermal transition, chemical structure, composition and topology affect the crystallization of block polymers. External components like plasticizers or fillers could modify the multiple crystallization of block copolymers. The thermal treatment is a key factor in developing two or more crystalline phases.